Penggunaan Strategi Pembelajaran Discovery Learning untuk Meningkatkan Keaktifan dan Hasil Belajar Siswa SD/MI - Anju Mayang Chairunnisa; Sekar Dea Lestari; Siti Sarah; Amiruddin Amiruddin; Aulia Febrianti Saragih; Fatimah Tanjung (Edumaspul: Jurnal Pendidikan, 2022)
This research aims to increase students' enthusiasm in carrying out social studies learning so that the desired student learning outcomes can be achieved, as for the method used in this study, namely in the form of qualitative research. The results of this study show that the use of Discovery Learning learning strategies in social studies subjects for SD/MI students can increase students' enthusiasm for learning and learning outcomes.